Wroxeter A Cultural and Social History of the Roman City. - White, Roger H. (Archaeopress Roman Sites Ser., 2022)
This book reflects on how people over time have viewed the abandoned Roman city of Wroxeter in Shropshire. It responds to three main artistic outputs: poetry, images and texts. It explores what locals and visitors thought of the site over time, and considers how access to the site has altered, impacting on who visits and what is understood.